The effect of cinnamon on polycystic ovary syndrome in a mouse model - Lei Dou; Yahong Zheng; Lu Li; Xiaowei Gui; Yajuan Chen; Meng Yu; Yi Guo (BMC, 2018)
Abstract Background Polycystic ovary syndrome (PCOS) is the most prevalent cause of anovulatory infertility and hyperandrogenism. Evidence favors insulin resistance and compensatory hyperinsulinemia as the predominant, perhaps primary, defects in PCOS. The use of insulin-sensitizing drugs has been shown to improve both the reproductive and the metabolic aspects of PCOS. Cinnamon has been found to have insulin sensitizing effect and improve menstrual cyclicity in women with PCOS. The aim of this study was to determine the effect and mechanism of cinnamon on PCOS using a dehydroepiandrosterone (DHEA) induced PCOS mouse model. Methods Prepubertal C57BL/6 mice (age 25 days) were raised to developed into control group, DHEA group and DHEA plus cinnamon group for 20 days. The stages of the estrous cycle were determined based on vaginal cytology; metabolic characteristics were examined by intraperitoneal glucose tolerance test and insulin tolerance test, the serum levels of hormones (testosterone, insulin, LH, FSH, IGF-1, IGFBP-1) were checked using enzyme-linked immunosorbent assay (ELISA) method, the ovarian morphology was observed by stained with hematoxylin and eosin. IGF-1 and IGFBP-1 expression in ovary were detected by immunohistochemical stain. Results Cinnamon restores the cyclicity and ovary morphology in PCOS mice model induced by DHEA. There are significant differences of serum level of total testosterone (0.033 ± 0.009 ng/ml), among control group, DHEA and cinnamon group (0.052 ± 0.011 ng/ml), and DHEA group (0.079 ± 0.015 ng/ml); There was an increasing tendency of serum FSH level from DHEA group (5.02 ± 0.31 ng/ml), DHEA and cinnamon group (5.81 ± 0.51 ng/ml), to control group (7.13 ± 0.74 ng/ml); and there was a decreasing trend of serum LH level from DHEA group (3.75 ± 0.57 ng/ml), DHEA and cinnamon group (1.35 ± 0.61 ng/ml), or control group (0.69 ± 0.34 ng/ml); serum insulin level is significantly higher in DHEA treated mice (1.61 ± 0.31 ng/ml) than control group (0.93 ± 0.19 ng/ml), or DHEA and cinnamon effect (1.27 ± 0.23 ng/ml) (p < 0.05). The DHEA group also has a higher serum IGF-1 level (0.35 ± 0.06 ng/ml) than control group (0.17 ± 0.04 ng/ml) or DHEA and cinnamon group (0.21 ± 0.05 ng/ml) (p < 0.05). While DHEA group has a lower IGFBP-1 level (5.5 ± 1.6 ng/ml) than control group (15.8 ± 2.1 ng/ml) or DHEA and cinnamon group (10.3 ± 2.5 ng/ml) (p < 0.05). Cinnamon also attenuates DHEA induced a higher IGF-1 and lower IGFBP-1 expression in ovary by immunohistochemistry. Conclusions These preliminary data suggest that cinnamon supplementation improves insulin resistance and may be a potential therapeutic agent for the treatment of PCOS.